Sticky plants and plant-based glues: potential for pest control - Bierman, Thijs V.; Choi, Young H.; Bezemer, T. Martijn (Frontiers in Plant Science, 2025)
Many vascular plants produce adhesive substances that may trap arthropods for their own protection, nutrition, and to engage in mutualistic relationships with predatory arthropods. While the role of stickiness in plant defense is well established, our understanding of the mechanisms and factors that determine the successful capture of arthropods by sticky plants and how we can utilize this knowledge to increase the sustainability of our agricultural practices is still limited. We review the literature on arthropod-trapping sticky plants and plant-based adhesive use in agriculture. There are many factors involved in the successful capture of arthropods by sticky plants, including: plant morphology, glue chemistry, the use of visual cues and volatiles to affect arthropod behavior, environmental factors, and adaptations of arthropods in their behavior, morphology, and chemistry to avoid being captured. Considering agricultural potential, using sticky crops as trap plants and ameliorating crops with sticky features could be useful for crop protection, but practical application is scarce. The same is true for the use of sticky plant specialist arthropod predators. Furthermore, plant-based adhesives are becoming more popular in agriculture for example, as glues for sticky traps, as sprayable adhesives for physical plant protection, and as carriers of botanicals and pesticides. So far, these adhesives see only small-scale use and are often less effective in the field than in the laboratory. Before plant stickiness and plant-based glues can be fully utilized for crop protection, several technological and resource related challenges must also first be overcome.